2014
DOI: 10.1007/s11145-014-9536-x
|View full text |Cite
|
Sign up to set email alerts
|

The relations between word reading, oral language, and reading comprehension in children who speak English as a first (L1) and second language (L2): a multigroup structural analysis

Abstract: Babayigit, S. (2015) The relations between word reading, oral language, and reading comprehension in children who speak English as a first (L1) and second language (L2): A multigroup structural analysis. Reading and Writing, 28 (4). pp. 527-544. ISSN 0922-4777 Available from: http://eprints.uwe.ac.uk/25337We recommend you cite the published version. The publisher's URL is: http://dx.doi.org/10.1007/s11145-014-9536-x Refereed: YesThe final publication is available at Springer via http://dx.doi.org/10.1007/s111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 36 publications
13
38
0
1
Order By: Relevance
“…While SWRT and C-test scores are highly correlated for the EAL learners, the regression analysis showed that the C-test scores explained variation in mathematics scores over and above what is explained by word decoding skills. Our finding that general language ability as measured by the C-test correlates significantly with reading comprehension levels of both L1 and L2 students furthers evidence stemming from previous pieces of research in English (Lesaux, Rupp, and Siegel 2007;Babayiğit 2014Babayiğit , 2015 and in Dutch (Droop and Verhoeven 2003). More importantly, it extends our knowledge of how general language ability might affect comprehension in the context of word-based mathematics problem solving for FLE and EAL students.…”
Section: Discussionsupporting
confidence: 84%
“…While SWRT and C-test scores are highly correlated for the EAL learners, the regression analysis showed that the C-test scores explained variation in mathematics scores over and above what is explained by word decoding skills. Our finding that general language ability as measured by the C-test correlates significantly with reading comprehension levels of both L1 and L2 students furthers evidence stemming from previous pieces of research in English (Lesaux, Rupp, and Siegel 2007;Babayiğit 2014Babayiğit , 2015 and in Dutch (Droop and Verhoeven 2003). More importantly, it extends our knowledge of how general language ability might affect comprehension in the context of word-based mathematics problem solving for FLE and EAL students.…”
Section: Discussionsupporting
confidence: 84%
“…It is notable that in this study EL1 and EAL groups were matched on word reading accuracy and speed, verbal memory and duration of formal schooling in England. These findings were confirmed in a subsequent study with a larger cohort of EAL learners (Babayiğit, 2015), suggesting that oral language skills could be a key factor in explaining the EAL gap in reading comprehension. Moreover, a study on Dutch-speaking bilingual learners found that controlling for weaker Dutch vocabulary of bilingual learners led to a secondlanguage advantage in reading comprehension (van Steensel et al, 2014).…”
Section: Comparison Of El1 and Eal Learners' English Oral Language Ansupporting
confidence: 55%
“…It is currently unclear whether the relations between oral language and reading comprehension are comparable for EL1 and EAL learners, which may in turn influence the developmental trajectories in reading comprehension over time (Farnia & Geva, 2013). The few studies that compared the pattern and strength of these relations between the first-language and second-language learners have reported mixed findings (e.g., Babayiğit, 2014Babayiğit, , 2015Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;Lesaux, Lipka, & Siegel, 2006;Trapman, van Gelderen, van Steensel, van Schooten, & Hulstijn, 2014;van Gelderen et al, 2003). For example, Trapman et al (2014) found that whereas receptive vocabulary, grammar and metacognition were strong predictors of reading comprehension in bilingual Dutch-speaking students, word reading fluency was the strongest predictor of monolingual reading comprehension.…”
Section: Comparisons Of Oral Language and Text Comprehension Relationmentioning
confidence: 99%
“…Specifically, it is hypothesized that bilingual language‐minority children might underperform in the instructional language compared with monolingual typical readers, but not in the foreign language literacy tasks. Despite the often‐reported heterogeneity in L2 exposure and in the L1 background, studies on bilingual language‐minority children have often analysed L2 language‐minority students as large groups (Babayiğit, ; Bellocchi et al, ) because of many other common features. For the purpose of the present study, we addressed the issue of assessing the pattern of strengths and weaknesses across measures of reading and writing in Italian and English, rather than differences in absolute levels of performance between bilinguals and monolinguals.…”
Section: The Present Studymentioning
confidence: 99%